European security since the fall of the Berlin Wall - Mérand, Frédéric, 1976-; Foucault, Martial, 1972-; Irondelle, Bastien (European Union studies., 2011)
"There have been dramatic changes to the landscape of European security in the twenty years since the fall of the Berlin Wall. The essays in European Security Since the Fall of the Berlin Wall collectively take stock of how approaches to security in Europe have changed, both in practice and in theory, since the end of the Cold War.